The action of SDZ 205,557 at 5-hydroxytryptamine (5-HT3 and 5-HT4) receptors. - Eglen, R. M. (1993)
1. The interaction of the novel antagonist, SDZ 205,557 (2-methoxy-4-amino-5-chloro benzoic acid 2-(diethylamino) ethyl ester), at 5-HT3 and 5-HT4 receptors has been assessed in vitro and in vivo. 2. In guinea-pig hippocampus and in the presence of 0.4 microM 5-carboxamidotryptamine, 5-HT4-mediated stimulation of adenylyl cyclase was competitively antagonized by SDZ 205,557, with a pA2 value of 7.5, and a Schild slope of 0.81. In rat carbachol-contracted oesophagus, 5-HT4-receptor mediated relaxations were surmountably antagonized by SDZ 205,557 with a similar pA2 value (7.3). This value was agonist-independent with the exception of (R)-zacopride, against which a significantly lower value (6.4) was observed. 3. In functional studies of 5-HT3 receptors, SDZ 205,557 exhibited an affinity of 6.2 in guinea-pig ileum compared with 6.9 at binding sites labelled by [3H]-quipazine in NG108-15 cells. In the anaesthetized, vagotomized micropig, SDZ 205,557 produced only a transient blockade of 5-HT4-mediated tachycardia. This contrasted with tropisetron, which was active for over 60 min after administration. The half-lives for the inhibitory responses of SDZ 205,557 and tropisetron were 23 and 116 min, respectively. 4. In conclusion, SDZ 205,557 has similar affinity for 5-HT3 and 5-HT4 receptors. The apparent selectivity observed in guinea-pig is due to the atypical nature of the 5-HT3 receptor in this species. The short duration of action of this novel antagonist may complicate its use in vivo. SDZ 205,557 should, therefore, be used with appropriate caution in studies defining the 5-HT4 receptor.